Slowing Down and Digging Deep: Teaching Students to Examine Interview Interaction in Depth (LEARNing Landscapes, 2021)
Teaching students to become critical consumers of interviews, which often serve as influential sources for learning and interpreting world events, is important in today’s information-rich world. This paper outlines an approach to teaching in-depth interviewing in which students examine excerpts from interviews (e.g., archival collections, oral histories, or media interviews) using the tools of ethnomethodology and conversation analysis to “slow down” and “dig deep” into the social aspects of interviews. Using two case examples from undergraduate and graduate classrooms, we illustrate how this approach helps students to notice how question-answer sequences unfold and encourages critical consumption and participation in interviews.
Keywords: qualitative interviewing; critical reflection; ethnomethodology; conversation analysis; slow ontology